A Compact UWB BPF with a Notch Band using Rectangular Resonator Sandwiched between Interdigital Structure - Yatindra Gaurav; R.K. Chauhan (Institute of Advanced Engineering and Science, 2017)
This paper presents a compact design of an ultra wide band bandpass filters with a notch band using interdigital structure. The aim of the design is to reduce the size of filter, reduce the complexity of the design, and improve the performance of filter response. The proposed filter comprises of a rectangular resonator sandwiched between Interdigital structures, with rectangular slot as defected microstrip structure at the input and output ports. This design has been used for the first time to achieve the above aim. The advantage with this design is that, it does not use any via or defected ground structure. The insertion loss of proposed filter, in passband between 3.1 GHz to 10.8 GHz, is less than 0.7dB, and for the notched band it is 21.5 dB centred at 7.9 GHz. The proposed filter is fabricated, tested and compared with simulated results. The proposed design was small in size with less complexity, and shows performance better than the other designs available in the literatures at this dimension.